Antipanic procedures reduce the strychnine-facilitated wild running of rats - de Paula, HMG; Hoshino, K. (Elsevier B.V., 2003)
Wild running (WR) behavior of rats seen in response to intense acoustic stimulation of audiogenic seizure-paradigm is very similar to the panic flight and can be facilitated by subconvulsive doses of strychnine. The present work aimed to test whether antipanic procedures, such as dorsal periaqueductal gray (dPAG) lesion and imipramine treatments, affect the strychnine-facilitated WR. In study 1, six Wistar male adult rats with electrolytic lesion of dPAG had their WR completely blocked, whereas it was facilitated in 50% of sham-lesioned control rats by a dose of 0.5 mg/kg of strychnine administered intraperitoneal. This effect was not reproduced with a higher strychnine dose (1.0 mg/kg). In study 2, the effects of imipramine were investigated by testing 36 rats under a dose of strychnine that induces WR in 50% of subjects. They were assigned into three experimental groups: imipramine treatments of 5.0 and 10.0 mg/kg, and infusions of saline. All these treatments were subchronical with three intraperitoneal injections within 24h. Imipramine (10.0mg/kg) reduced the incidence of WR in comparison to the saline results. It is concluded that strychnine-facilitated WR is reduced by antipanic procedures and, therefore, can be viewed as a manifestation closely related to panic. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: panic; strychnine; wild running; periaqueductal gray; imipramine; rat